Faith-Based Leadership and Women’s Empowerment in the Aisyiyah Organization - Nurdiana, Ratna; Emeraldien, Fikry Zahria; Chen, Huey-Rong (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This article discusses faith-based female leadership within Aisyiyah, a long-standing autonomous organization under Muhammadiyah actively engaged in religion, education, health, economy, environment, and social welfare. Aisyiyah practices a distinctive and contextually grounded leadership model firmly rooted in religious values, community participation, and grassroots empowerment. This study employs a descriptive qualitative approach with thematic analysis, drawing on data from internal documentation, activity reports, and findings from FGD and interviews with regional leaders. The results show that Aisyiyah has successfully integrated leadership structures from the central level to the village level, involving thematic councils in education, preaching, cadre development, economy, health, social welfare, law, culture, and environment, all of these led by women. This cross-council strategy fosters effective collaboration, addresses the challenge of leadership regeneration, and strengthens women’s contributions to local development. The findings also affirm that organizational forums function as reporting platforms, deliberative spaces for vision strengthening, policy evaluation, sustainable cadre development, and participatory communication. By showcasing leadership practices rooted in Islamic values and women’s empowerment within a modern organizational context, this article contributes significantly to the discourse on Islamic women’s organizations, organizational communication, civil society governance, and gender mainstreaming at the community level.